Britain's forgotten military medical school at Fort Pitt, Kent (1860–1863). (November 2022) - Bowen, Melissa; Whiston, Benjamin; Cooper, Max
This article considers the history of Fort Pitt (1780-1922), its military hospital (founded 1814) and, in particular, its Army Medical School (1860–63). The museum and library were the work of the hospital's first directors: Dr David MacLoughlin and Sir James McGrigor, the latter the renowned reformer of military medical education. Central to the foundation of the medical school was Florence Nightingale who visited the site in 1856. The school opened in 1860 with five sets of students attending before it was transferred in 1863 to the Royal Victoria hospital, Netley, Hampshire. Fort Pitt was a "practical" medical school with students attending for 4-9 months of clinical experience. This included "instruction in tropical medicine" delivered by members of the Indian Medical Service. The foundation of a military medical school fulfilled an ambition dating back to at least 1796. Nightingale's role (exerted through Sidney Herbert) was omitted from contemporary newspaper reports. Fort Pitt continued as a military hospital until 1922 when it was converted to a school. The medical school constitutes a landmark in British military medicine, a response to the failure of British medical care in the Crimean war (1853–1856) and a forgotten legacy of Florence Nightingale.